Analysis of Car Parking Space Capacity at Banjarnegara Culinary Center - Anggriawan, Eri; Nardiansyah, Afrie (Jurnal Indonesia Sosial Sains, 2025)
Banjarnegara’s culinary center, a hub for MSME growth, faces parking inefficiencies due to inadequate planning, risking visitor discomfort and revenue loss. Despite regional infrastructure investments, parking capacity remains unstudied for future scalability. This research analyzes current parking capacity, evaluates user satisfaction, and designs an optimized layout to address projected demand. Field observations (17–23 February 2025) tracked vehicle volume, accumulation, and duration, while surveys (325 respondents) assessed safety/satisfaction. Data were analyzed using SRP metrics, SPSS validity/reliability tests, and AutoCAD simulations for parking patterns. The existing 18-SRP capacity was overwhelmed (peak: 28 vehicles, index: 150%). A 90° angled layout increased capacity to 22 SRPs. Surveys confirmed validity (r-calculated > r-table) and reliability (α=0.936), with 60% of respondents citing inadequate space. Projections show capacity deficits by 2028. Urgent adoption of the 90° pattern and tech-based solutions (e.g., sensors) is recommended to align with Banjarnegara’s e-parking policies and support sustainable tourism growth.